2009
DOI: 10.1257/aer.99.3.1006
|View full text |Cite
|
Sign up to set email alerts
|

Under the Weather: Health, Schooling, and Economic Consequences of Early-Life Rainfall

Abstract: We examine the effect of early-life rainfall on the health, education, and socioeconomic outcomes of Indonesian adults. We link historical rainfall for each individual's birth year and birth location with adult outcomes from the 2000 Indonesia Family Life Survey (IFLS). Higher early-life rainfall has large positive effects on the adult outcomes of women, but not of men. Women with 20 percent higher rainfall (relative to the local norm) are 0.57 centimeters taller, complete 0.22 more schooling grades, and live … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
527
9
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 885 publications
(577 citation statements)
references
References 34 publications
38
527
9
3
Order By: Relevance
“…Bohra-Mishra et al (2014), described above, found a significant nonlinear effect of rainfall levels on migration. This is consistent with at least one other study from Indonesia that documented the effects of early-life rainfall levels on later-life health outcomes (Maccini and Yang 2009). However, other research suggests that delays in monsoon onset have a particularly strong and significant impact on rice and maize production, which plays a key role in the Indonesian economy (Naylor et al 2002(Naylor et al , 2007 and has important consequences for household economic status (Skoufias et al 2012).…”
Section: Current Studysupporting
confidence: 90%
“…Bohra-Mishra et al (2014), described above, found a significant nonlinear effect of rainfall levels on migration. This is consistent with at least one other study from Indonesia that documented the effects of early-life rainfall levels on later-life health outcomes (Maccini and Yang 2009). However, other research suggests that delays in monsoon onset have a particularly strong and significant impact on rice and maize production, which plays a key role in the Indonesian economy (Naylor et al 2002(Naylor et al , 2007 and has important consequences for household economic status (Skoufias et al 2012).…”
Section: Current Studysupporting
confidence: 90%
“…on September 8, 2016 http://science.sciencemag.org/ contexts, adverse rainfall in the year of birth lowers adult female health outcomes and educational attainment (71), and droughts experienced by toddlers lower childhood growth and education (30,72). These rainfall-related impacts likely operate through agricultural income loss and lowered nutrition; however, our understanding of these channels is generally weak, and work is needed to parse out direct physiological impacts from economic factors and behavioral responses.…”
Section: Research | Reviewmentioning
confidence: 99%
“…However, one case from Bangladesh shows that non-poor households face a larger share of shocks, especially a larger share of asset shocks than the poor do (Santos, Sharif, Rahman, & Zaman, 2011). The shocks can cause substantial short-run losses in assets, incomes (Elbers et al, 2007;Morris et al, 2002;Thomas et al, 2010), and health (Dercon & Hoddinott, 2003;Maccini & Yang, 2009), and could have long-run negative effects on a household's livelihood (Thomas et al, 2010). The adverse events can also cause the household to have a higher vulnerability to poverty (Imai et al, 2011;Santos et al, 2011).…”
Section: Empirical Evidence From the Literature On Shock Recoverymentioning
confidence: 99%
“…Using also Indonesian Family Life Surveys data from 2000, Maccini and Yang (2009) examine the effect of rainfall variation around the time of birth on the health, education and socioeconomic outcomes of Indonesian adults born between 1953 and 1974. They find that the higher amount of rainfall during a person's early life has positive effects on the outcomes of women but not men.…”
Section: Empirical Evidence From the Literature On Shock Recoverymentioning
confidence: 99%